Targeting pathogenic fibroblast-like synoviocyte subsets in rheumatoid arthritis - Hongyan Qian; Chaoqiong Deng; Shiju Chen; Xinwei Zhang; Yan He; Jingying Lan; Aodi Wang; Guixiu Shi; Yuan Liu (Arthritis Research & Therapy)
Abstract Fibroblast-like synoviocytes (FLSs) play a central role in RA pathogenesis and are the main cellular component in the inflamed synovium of patients with rheumatoid arthritis (RA). FLSs are emerging as promising new therapeutic targets in RA. However, fibroblasts perform many essential functions that are required for sustaining tissue homeostasis. Direct targeting of general fibroblast markers on FLSs is challenging because fibroblasts in other tissues might be altered and side effects such as reduced wound healing or fibrosis can occur. To date, no FLS-specific targeted therapies have been applied in the clinical management of RA. With the help of high-throughput technologies such as scRNA-seq in recent years, several specific pathogenic FLS subsets in RA have been identified. Understanding the characteristics of these pathogenic FLS clusters and the mechanisms that drive their differentiation can provide new insights into the development of novel FLS-targeting strategies for RA. Here, we discuss the pathogenic FLS subsets in RA that have been elucidated in recent years and potential strategies for targeting pathogenic FLSs.